Decoding Organizational Culture Dynamics in Bureaucratic Reform: A Phenomenological Study Among Indonesian Public Sector Employees - Indira Yuana; Rince Tambunan; Abdul Syaban; Muh. Nur; Asraf (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
Organizational culture in the public sector plays a critical role in driving bureaucratic reform and institutional transformation. In Indonesia, however, entrenched hierarchical norms, generational value gaps, and employment status disparities between civil servants and non-civil servants (contractual staff) pose significant challenges to inclusive and adaptive cultural change. This study explores how employees interpret and respond to these cultural shifts through a phenomenological lens. Using Interpretative Phenomenological Analysis, data were collected from 12 informants across central and local government agencies, representing diverse generations and employment statuses. The findings reveal five key themes: the transition from bureaucratic to adaptive cultures, internal employee challenges, the role of transformational leadership, polarization based on employment status, and aspirations for inclusivity. Non-civil servant employees often experience exclusion and limited recognition, while younger generations face structural resistance to innovation. Despite reforms, informal norms and unequal treatment persist, highlighting the gap between espoused values and actual practice. This study underscores the importance of leadership consistency, inclusive HR strategies, and culturally sensitive change management. By capturing employees’ lived experiences, this research contributes to a deeper understanding of organizational culture in the public sector. It offers strategic insights for more equitable and context-responsive bureaucratic transformation in developing countries.